PENDAPATAN PERKAPITA DAN PERSERTIPIKATAN TANAH (STUDI DI KOTA SEMARANG DAN KABUPATEN WONOGIRI) - Prasetyo, Priyo Katon; ., Sudibyanung (MAGISTRA, 2011)
Land, functioning as both producing and spatial factors, needs a legal guarantee through the landregistration process. The land registration carried out so far represents the active role of the government andis not the inniative of the society. The previous research showed that the societies motivation to sporadicallyregister their land was affected by the level of income. This would mean that the more income the society got,the more highly motivated they registered their land and vice versa. However, the above result was only basedon the micro income or the individual income of the society. The research based on the macro or percapitaincome of the society has not been carried out. Therefore, the research dealing with the macro income relatedto the societys motivation on registering their lands needs to be done.  The research is aimed at knowing theaffect of the societys percapita income on registering their lands by a sporadic way. Two locations were chosen in this research, Semarang City and Wonogiri Regency with the assumptionthat the Semarang City populations income tends to be higher than that of the Wonogiri Regency populations.The research belongs to the appied research. The secondary data were taken from the related  institutions  suchas the Statistitics Central Office of the Central Java Province, the Land Office of the Central Java Province, theLand Office of the Semarang City Government and the Land Office of Wonogiri Regency.The statistic analysis using ARCH method showed that the macro income of the society did not affectsignificantly (95% of reliability level) on the sporadic land registration for both Semarang and Wonogiripopulation.  The variable of percapita income had the probability of more than 0,05. Furthermore, the resultalso showed that the economic apriori test was able to explain that there was a reciprocal relation. The moreincome they had, the less motivated they registred their lands.____________Key words: land, motivation, land registration, sporadic, percapita income.